Oxford Photo Dictionary - Edited By Taylor, Jane (China Oxford University Press, 1991)
A topic-based, full-colour photo dictionary
Include Color Illustrations and Index
Keywords: Picture dictionaries, English -- Encyclopedias and dictionaries -- Picture dictionaries, Khmer